ON THE ASSESSMENT OF MATHEMATICAL COMPETENCIES FOR SOLVING NON-LINEAR EQUATIONS - Gocheva-Ilieva, Snezhana Georgieva; Iliev, Iliycho Petkov; Ivanov, Atanas Valev (MATTER: International Journal of Science and Technology, 2020)
The process of learning and acquiring mathematics by students is inextricably linked with the need to measure the achieved level of their knowledge and skills at each stage of education. The aim of the study is to propose a methodological approach for evaluating students’ mathematics competencies in engineering degrees, developed in accordance with the results of the European Erasmus+ project Rules_Math. A competency assessment model is presented that includes three main components: multiple-choice test, tasks to solve and a small practical project on a topic from the curriculum for first-year students. The multiple-choice test aims to assess students’ understanding of the basic notions, concepts, and methods in the field. Solving problems should measure the level of knowledge and skills acquired. The practical project could evaluate the students’ ability to apply what has been learned to solve practice-oriented tasks. It is recommended to use mathematical software. The approach is demonstrated with a specific example of assessing mathematical competencies for solving non-linear equations of a single variable. Answers and solutions are also provided. The presented methodology can be used by professors and tutors in higher education institutions to update the assessment of students’ competencies in mathematics.